(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Past decades, the corporate needs help from educational institute placement cell for employee recruitment. Nowadays, the process is by various sources like direct walk-in, online mode, consultancies, etc. Especially, the engineering educations, the unemployment ratio is equal to the out candidates; However, the domain selection, position, is not fully depends on the candidates profile. Various reviews are studied to analyze the recruitment process of Educational Institutions. Based on the industry reports, the IT and BPO sectors are reviewed for various educational institutes. Nowadays, educational institutions are offering various courses and training for recruitment process. The written test, group discussion and technical interview is analyzed with number of candidates; after, the personal interview session will desired the selected candidates. Few students are selected on learning period; after they continued the studies. The dataset is collected from various sources of placement database like web pages of educational institutes, corporate, consultancies, reviewers etc. This study focusing on the recent trends, and problems and this reviewed to motivate the candidates to improve skills, selecting exact domain and attending fearless interview. This analysis is done by Chi Square Test calculations. Depends on the collected data, the analysis report shows the result, which helps to analyze the various review analysis of placement recruitment process in educational institutions.